The alliance : managing talent in the networked age - Hoffman, Reid. (Harvard Business Review Press, 2014)
"For most of the 20th century, the relationship between employers and employees in the developed world was all about stability and lifetime loyalty. That has recently changed, giving way to a transactional, laissez-faire approach that serves neither party well. A new arrangement is needed, the authors argue--one built on alliance (usually temporary) and reciprocity. The high-tech start-up community of Silicon Valley is pointing the way--and companies that wish to be similarly agile and entrepreneurial can learn valuable lessons from its example. Under the new compact, both employer and employee seek to add value to each other. Employees invest in the company's adaptability; the company invests in employees' employability. Hoffman (a cofounder of LinkedIn), Casnocha (a technology entrepreneur), and Yeh (an entrepreneur and angel investor) outline three simple, straightforward ways in which companies can make the new compact tangible and workable. These are (1) hiring employees for explicit "tours of duty," (2) encouraging, even subsidizing, employees' efforts to build networks outside the organization, and (3) establishing active alumni networks that will enable career-long relationships with employees after they've moved on. In the war for talent, such a compact can be a secret weapon that helps you fill your ranks with the creative, adaptive superstars who fuel entrepreneurial success"--